A modular approach to highly functionalized 3-sulfonylfurans via conjugate addition of 3-cyclopropylideneprop-2-en-1-ones with sodium sulfinates and sequential 5-endo-trig iodocyclization. Issue 9 (21st June 2017) - Miao, Maozhong; Xu, Huaping; Luo, Yi; Jin, Mengchao; Chen, Zhengkai; Xu, Jianfeng; Ren, Hongjun
Abstract : Conjugate addition of 3-cyclopropylideneprop-2-en-1-ones with sodium sulfinates and sequential 5- endo -trig iodocyclization to afford valuable 3-sulfonylfurans. Abstract : A highly efficient conjugate addition and 5- endo -trig cyclization reaction of 3-cyclopropylideneprop-2-en-1-ones with sodium sulfinates in the presence of iodine is described. A wide variety of densely functionalized 3-sulfonylfurans are furnished by single-step and one-pot methods, respectively. The results of such postcyclization modifications are also presented.